MAQASID SYARIAH AND THE ETHICAL TURN IN ISLAMIC EDUCATIONAL MANAGEMENT - Wildan Miftahussurur; Abdul Goffar; Abdul Haq As (BAMALA Institute, 2025)
This article examines the ethical turn in Islamic educational management by positioning Maqasid Syariah as an operational ethical framework rather than a purely normative or legal construct. Responding to the limitations of technocratic and performance-driven governance models, the study argues that contemporary Islamic educational institutions require a value-oriented approach capable of integrating managerial effectiveness with moral responsibility. Using a conceptual and analytical methodology, the article synthesises classical and contemporary Maqasid scholarship with theories of ethical and values-based educational management. The analysis demonstrates that Maqasid Syariah functions as an ethical architecture that reorients managerial decision-making towards human dignity, intellectual development, social justice, and long-term sustainability. The study further illustrates how this ethical framework can be operationalised across key domains of educational management, including leadership, human resource management, curriculum governance, quality assurance, and financial stewardship. By embedding ethical considerations into routine managerial processes, Maqasid Syariah enables Islamic educational institutions to navigate modern governance demands without compromising their moral and educational missions. The article contributes to the literature by bridging the gap between normative Islamic ethics and practical management, offering a conceptual foundation for ethically coherent and contextually responsive educational governance.